The Effect of Job Satisfaction and Fingerprint Attendance System on Employee Work Discipline: Loyalty as A Moderation Variable - Henry Feonale; John Edward Harly Jacob Foeh; Thomas Ola Langoday (CV. Namora dan Riona Bersaudara, 2026)
This study aims to analyze the influence of job satisfaction and the fingerprint attendance system on employee work discipline, as well as the moderating role of loyalty among volunteer civil servants (ASN) within the Kupang City Government, East Nusa Tenggara. A quantitative approach with an explanatory research design was employed in this study. Data were collected through questionnaires distributed online to 146 respondents selected using purposive sampling. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 3.0. The results indicate that job satisfaction and the fingerprint attendance system did not significantly affect employee work discipline. In addition, loyalty was unable to moderate the relationship between job satisfaction and work discipline, as well as between the fingerprint attendance system and work discipline. However, loyalty showed a significant positive effect on work discipline, suggesting that employees with stronger organizational loyalty tend to demonstrate better discipline in carrying out their responsibilities. These findings imply that employee work discipline in government institutions is influenced more by organizational commitment, supervision, and institutional culture than by employee satisfaction or attendance technology alone. This study also contributes to the development of public sector human resource management literature, particularly regarding employee work behavior and organizational discipline.